Latest update on the use of recombinant growth factors for periodontal regeneration: existing evidence and clinical applications - Anahat Khehra; Takahiko Shiba; Chia-Yu Chen; David M. Kim (Therapeutic Advances in Chronic Disease)
Growth factors were introduced to increase predictability in periodontal regeneration and have since been widely applied in dentistry. This narrative review article highlights histological and latest findings of recombinant human platelet-derived growth factor-BB (rhPDGF-BB) and recombinant human fibroblast growth factor-2 (rhFGF-2) for periodontal regeneration. rhPDGF-BB enhances the proliferation and chemotaxis of periodontal ligament and alveolar bone cells. The optimal dose for rhPDGF-BB, in combination with beta-tricalcium phosphate, is 0.3 mg/ml. It is approved in the United States, Canada, and Taiwan for use in periodontal regeneration and treatment of gingival recession. rhFGF-2 promotes periodontal wound healing through mitogenic and angiogenic effects on mesenchymal cells in the periodontal ligament. It is approved in Japan at an optimal dose of 0.3% for periodontal regeneration in intrabony defects. Both recombinant growth factors show histological evidence of new bone, cementum, and periodontal ligament. Clinical studies demonstrate improved clinical attachment levels and defect resolution for treating intrabony and furcation periodontal defects. Presented clinical cases and consensus reports may serve as a reference for clinicians. rhPDGF-BB and rhFGF-2 are safe and effective biologics that can be applied to improve the outcomes of periodontal regeneration.